Surface modification method of silicon-carbon negative electrode material, modified silicon-carbon negative electrode material, negative electrode plate and lithium ion battery
By modifying the surface of the silicon carbon negative electrode material, a stable SEI film is formed, which solves the performance problems caused by volume changes during charging and discharging, and significantly improves the first-time Coulomb efficiency and cycle stability of the battery.
Patent Information
- Application Number
- CN202510004529.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-08
AI Technical Summary
The volume of silicon carbon anode material changes greatly during charging and discharging, resulting in poor cycling performance and electrochemical stability, which limits its practical application.
The silicon carbon negative electrode material is modified by surface modification method, and a stable solid electrolyte interface film (SEI film) is formed on its surface to inhibit the volume expansion of silicon during charge and discharge. The method includes performing a first sintering treatment under an inert atmosphere condition, followed by atomizing the modifier solution and performing a second sintering treatment under a high pressure sintering condition to form a fluorinating agent-modified carbon layer.
By forming a stable SEI film, the first Coulomb efficiency and cycle stability of the silicon carbon anode material are significantly improved, and the volume expansion of silicon is suppressed, thereby improving the overall performance of lithium-ion batteries.
Smart Images

Figure CN119786580A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries and relates to negative electrode materials for lithium ion batteries, and specifically relates to a surface modification method for silicon-carbon negative electrode materials, modified silicon-carbon negative electrode materials, negative electrode sheets and lithium ion batteries. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Silicon-carbon anode materials, as negative electrode materials for lithium-ion batteries, have attracted widespread attention due to their high theoretical capacity (about 10 times that of graphite). However, silicon has a large volume change during charging and discharging, resulting in poor cycle performance and electrochemical stability, which limits its practical application. Therefore, silicon-carbon anode materials need to be modified to improve their electrochemical performance. Summary of the invention
[0004] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a surface modification method for silicon-carbon negative electrode materials, modified silicon-carbon negative electrode materials, negative electrode sheets and lithium-ion batteries. After the silicon-carbon negative electrode materials are modified by the surface modification method provided by the present invention, a layer of stable solid electrolyte interface film (SEI film) can be formed through electrochemical reaction. The volume expansion of internal silicon during the charge and discharge process is suppressed by the stable solid electrolyte interface film (SEI film), thereby improving the first coulombic efficiency and cycle stability of the battery.
[0005] In order to achieve the above object, the technical solution of the present invention is:
[0006] In a first aspect, a surface modification method of a silicon-carbon negative electrode material comprises the following steps:
[0007] Under inert atmosphere conditions, heating the silicon-carbon negative electrode material to 500-1000° C. to perform a first sintering treatment to obtain a sintered silicon-carbon negative electrode material;
[0008] The modifier solution is atomized to the sintered silicon-carbon negative electrode material, and then pressurized to a gauge pressure of 80-100 kPa, heated to 350-650°C, and subjected to a second sintering treatment; wherein the modifier is PF5, CF2=CF2, sodium fluoride, ammonium fluoride, etc.
[0009] The present invention firstly performs a first sintering treatment on the silicon-carbon negative electrode material to improve the density, strength and hardness of the material to improve the physical and chemical properties of the material, then coats the modifier solution on the surface of the silicon-carbon negative electrode material by atomizing the modifier solution, and then modifies the coated carbon layer with PF5, CF2=CF2, sodium fluoride, ammonium fluoride, etc. under high-pressure sintering conditions, thereby forming a fluorinating agent-modified carbon layer on the surface of the silicon-carbon negative electrode material. The carbon layer modified by the fluorinating agent can construct a stable solid electrolyte interface film through electrochemical action, thereby being able to inhibit the volume expansion of silicon during the charging and discharging process, thereby improving the first coulomb efficiency and cycle stability of the battery.
[0010] The inert atmosphere condition described in the present invention refers to a gas atmosphere formed by an inert gas such as nitrogen, helium, or neon.
[0011] The gauge pressure mentioned in the present invention refers to the pressure based on the atmospheric pressure, which is greater than the pressure of the atmospheric pressure and is generally measured by a pressure gauge.
[0012] In some embodiments, in the modifier solution, the mass ratio of the modifier to the solvent is (0.1-2):1.
[0013] In some embodiments, the solvent used in the modifier solution is a liquid alcohol organic substance, a liquid ketone organic substance, a liquid nitrile organic substance, or an organic substance capable of dissolving fluorine-containing substances, such as tetrahydrofuran or dimethyl sulfoxide. Specifically, the liquid alcohol organic substance may be methanol, ethanol, etc. Specifically, the liquid ketone organic substance may be acetone, etc. Specifically, the liquid nitrile organic substance may be acetonitrile, etc. Specifically, the organic substance capable of dissolving fluorine-containing substances may be tetrahydrofuran, dimethyl sulfoxide, etc.
[0014] In some embodiments, the first sintering treatment lasts for 24 to 48 hours.
[0015] In some embodiments, the mass ratio of the modifier to the sintered silicon-carbon negative electrode material is (0.09-0.70):(0.01-1.0), preferably (0.09-0.70):(0.2-0.5).
[0016] In some embodiments, the mass ratio of the modifier solution to the sintered silicon-carbon negative electrode material is 1:(0.01-1.0), preferably 1:(0.2-0.5).
[0017] In some embodiments, the second sintering treatment lasts for 12 to 72 hours.
[0018] In a second aspect, a modified silicon-carbon negative electrode material is obtained by the surface modification method described in the first aspect of the present invention.
[0019] In a third aspect, a negative electrode sheet includes a current collector and an active layer attached to a surface of the current collector, wherein the active material in the active layer is the modified silicon-carbon negative electrode material described in the second aspect of the present invention.
[0020] In some embodiments, the modified silicon-carbon negative electrode material is added to a solvent, mixed evenly with a conductive agent, a binder, and a thickener to obtain a slurry, and the slurry is applied to the surface of the current collector and dried. Specifically, the conductive agent includes but is not limited to graphite, conductive carbon black, etc. Specifically, the binder can be SBR (styrene-butadiene rubber). Specifically, the thickener can be CMC (carboxymethyl cellulose), etc.
[0021] In a fourth aspect, a lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the negative electrode sheet described in the third aspect of the present invention.
[0022] In some embodiments, the active material of the positive electrode sheet may be lithium nickel cobalt manganese oxide.
[0023] The beneficial effects of the present invention are:
[0024] The surface modification method of the silicon-carbon negative electrode material provided by the present invention can modify the carbon layer on the surface of the silicon-carbon negative electrode material with modifiers such as PF5, CF2=CF2, sodium fluoride, and ammonium fluoride, so that the surface of the carbon layer has fluoride, which can react with lithium in the electrolyte to generate a stable solid electrolyte film such as lithium fluoride, which can effectively inhibit the volume expansion of silicon during the charge and discharge process and significantly improve the first coulomb efficiency and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0026] Figure 1 Schematic diagram of the structure of the silicon-carbon negative electrode material after surface modification in an embodiment of the present invention. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0028] Example 1
[0029] A surface modification method for a silicon-carbon negative electrode material comprises the following steps:
[0030] (1) A modifier solution was prepared in a mass ratio of 1:1, wherein the modifier used was PF5 and the organic solvent was methanol.
[0031] (2) The silicon-carbon negative electrode material is placed in a reactor, and an inert gas is introduced to sinter the material in an environment of 900°C for 24 hours.
[0032] (3) The silicon-carbon negative electrode material sintered in step (2) and the modifier solution prepared in step (1) are gasified and atomized and transferred into a gasification chamber at a solid-liquid ratio of 0.5:1 (mass ratio), so that the modifier solution is evenly coated on the surface of the silicon-carbon negative electrode material.
[0033] (4) The silicon-carbon negative electrode material with the surface-coated modifier solution obtained in step (3) is transferred to a tube furnace, and the pressure in the tube furnace is set to 100 kPa, the temperature is set to 450° C., and the sintering time is set to 48 h; a surface-modified silicon-carbon negative electrode material having a structure as shown in FIG. Figure 1 shown.
[0034] Example 2
[0035] A surface modification method for a silicon-carbon negative electrode material comprises the following steps:
[0036] (1) A modifier solution was prepared in a mass ratio of 2:1, wherein the modifier used was PF5 and the organic solvent was methanol.
[0037] (2) The silicon-carbon negative electrode material is placed in a reactor, and an inert gas is introduced to sinter the material in an environment of 900°C for 24 hours.
[0038] (3) The silicon-carbon negative electrode material sintered in step (2) and the modifier solution prepared in step (1) are gasified and atomized and transferred into a gasification chamber at a solid-liquid ratio of 0.5:1 (mass ratio), so that the modifier solution is evenly coated on the surface of the silicon-carbon negative electrode material.
[0039] (2) The silicon-carbon negative electrode material and the modifier solution prepared in (1) are gasified and atomized and transferred into a gasification chamber at a solid-liquid ratio of 0.5:1 (mass ratio), so that the modifier is evenly coated on the surface of the silicon-carbon negative electrode material; and then cooled and deposited to obtain the silicon-carbon negative electrode material coated with the surface modifier.
[0040] (4) The silicon-carbon negative electrode material with the surface-coated modifier solution obtained in step (3) is transferred to a tube furnace, and the pressure in the tube furnace is set to 100 kPa, the temperature is set to 650° C., and the sintering time is set to 24 h; a surface-modified silicon-carbon negative electrode material having a structure as shown in FIG. Figure 1 shown.
[0041] Example 3
[0042] A surface modification method for a silicon-carbon negative electrode material comprises the following steps:
[0043] (1) A modifier solution was prepared at a mass ratio of 0.5:1, wherein the modifier used was PF5 and the organic solvent was methanol.
[0044] (2) The silicon-carbon negative electrode material is placed in a reactor, and an inert gas is introduced to sinter the material in an environment of 900°C for 24 hours.
[0045] (3) The silicon-carbon negative electrode material sintered in step (2) and the modifier solution prepared in step (1) are gasified and atomized and transferred into a gasification chamber at a solid-liquid ratio of 0.2:1 (mass ratio), so that the modifier solution is evenly coated on the surface of the silicon-carbon negative electrode material.
[0046] (4) The silicon-carbon negative electrode material with the surface-coated modifier solution obtained in step (3) is transferred to a tube furnace, and the pressure in the tube furnace is set to 100 kPa, the temperature is set to 350° C., and the sintering time is set to 72 h; a surface-modified silicon-carbon negative electrode material having a structure as shown in FIG. Figure 1 shown.
[0047] Comparative Example 1
[0048] The silicon-carbon negative electrode material used in this comparative example 1 is a silicon-carbon negative electrode material that has not undergone surface modification. It is placed in a tubular furnace, and inert gas nitrogen is introduced. The temperature of the tubular furnace is set to 450°C and the sintering time is 48 hours; a silicon-carbon negative electrode material that has only undergone sintering treatment and has not undergone surface modification can be obtained.
[0049] Comparative Example 2
[0050] The silicon-carbon negative electrode material used in this comparative example 2 is a silicon-carbon negative electrode material that has not been subjected to surface modification treatment and sintering treatment.
[0051] The test method is as follows:
[0052] The silicon-carbon negative electrode material is dissolved in water with graphite, conductive carbon black, CMC and SBR and stirred to form a negative electrode slurry, wherein the appropriate ratio of the silicon-carbon negative electrode material, graphite, conductive carbon black, CMC and SBR is 5%:91.5%:0.5%:1.2%:1.8%; the stirred negative electrode slurry is coated on the negative electrode current collector, dried to form a negative electrode sheet, and the negative electrode sheet is rolled, slit and die-cut; lithium nickel cobalt manganese oxide, conductive agent and PVDF are dissolved in NMP and stirred to form a positive slurry, wherein lithium nickel cobalt manganese oxide (NCM900505, polycrystalline), conductive agent and PVDF are The suitable ratio of the agent and PVDF is 96%:1.5%:2.5%. The prepared positive electrode slurry is coated on the positive electrode collector and dried to form a positive electrode sheet, and the positive electrode sheet is rolled, slit and die-cut; the positive electrode sheet, the negative electrode sheet, the separator (a base film of PE material with a thickness of 7μm, a single-sided glue coating thickness of 2μm, and a ceramic coating thickness of 3μm) and the electrolyte (LiPF6: 14.50%, EC: 23%, EMC: 54.50%, FEC: 6%, DTD: 1.5%, TMSP: 0.50%) are assembled into a soft-pack battery.
[0053] (I) The same steps of formation, volume separation, etc. were carried out for the embodiments and comparative examples implemented in the present invention, and the data during the process were recorded. The data records are shown in Table 1.
[0054] Table 1
[0055] First discharge capacity (mAh / g) First efficiency (%) Example 1 222.72 91.41% Example 2 222.45 91.38% Example 3 221.99 91.39% Comparative Example 1 217.8 89.38% Comparative Example 2 217.3 89.14%
[0056] By analyzing the process data of the embodiments and comparative examples, it can be concluded that the silicon-carbon negative electrode material surface-modified by a modifier can improve its first discharge capacity and first efficiency in a soft-pack battery cell.
[0057] (ii) After the fixed capacity, one of the soft-pack batteries corresponding to the groups of the embodiments and comparative examples is selected for disassembly and testing, and the thickness of its negative electrode sheet is recorded as D1. Then, one of each group of soft-pack batteries is selected for 5 cycles (the test conditions during the cycle test are: current: 1C / 1C@25±1℃ in an oven@voltage range: 2.75-4.25V) for charge and discharge; after the charge and discharge, the soft-pack battery is fully charged, and then disassembled again to test the thickness D2 of the negative electrode sheet after the cycle, and then the rebound rate of each group after full cycle is calculated (rebound rate calculation (D2-D1) / D1*100%). The test results are shown in Table 2.
[0058] Table 2 Rebound rate of negative electrode cycle test
[0059] D1(μm) D2(μm) Rebound rate (%) Example 1 134.32 140.90 4.89% Example 2 133.56 140.37 5.09% Example 3 134.42 141.54 5.29% Comparative Example 1 134.96 143.59 6.39% Comparative Example 2 135.18 144.24 6.70%
[0060] By measuring the negative electrode rebound rate of the soft-pack battery cells processed by the embodiment and the comparative example under the same test conditions, it can be obtained that the silicon-carbon negative electrode material surface-modified by a fluorination agent can be used in the soft-pack battery cells to improve the rebound rate of the negative electrode plate, that is, the use of the surface modifier can inhibit the expansion of the silicon-carbon material to a certain extent.
[0061] (III) Cyclic performance test was conducted on the corresponding groups of soft-pack batteries of each embodiment and comparative example after constant capacity, and the test conditions were: charge and discharge voltage range was 2.75-4.25V, temperature was 25±3.0℃, and charge and discharge rate was 1.0C / 1.0C. The test results are shown in Table 3.
[0062] Table 3 Cyclic performance test results
[0063]
[0064] By measuring the capacity retention rate of the soft-pack batteries manufactured in the embodiments and comparative examples after a certain number of cycles under the same test conditions, it can be obtained that the silicon-carbon negative electrode material surface-modified by a fluorination agent can be used in the soft-pack batteries to improve the cycle retention rate of the soft-pack batteries, that is, by inhibiting the expansion of the silicon-carbon material, it can also improve the cycle stability of the soft-pack batteries in the batteries.
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A surface modification method for a silicon-carbon negative electrode material, characterized in that: The steps include: Under inert atmosphere conditions, heating the silicon-carbon negative electrode material to 500-1000° C. to perform a first sintering treatment to obtain a sintered silicon-carbon negative electrode material; The modifier solution is atomized to the sintered silicon-carbon negative electrode material, and then pressurized to a gauge pressure of 80-100 kPa, heated to 350-650° C., and subjected to a second sintering treatment; wherein the modifier is PF5, CF2=CF2, sodium fluoride or ammonium fluoride.
2. The surface modification method of the silicon-carbon negative electrode material according to claim 1, characterized in that: In the modifier solution, the mass ratio of the modifier to the solvent is (0.1-2):
1.
3. The surface modification method of the silicon-carbon negative electrode material according to claim 1, characterized in that: In the modifier solution, the solvent used in the modifier solution is liquid alcohol organic matter, liquid ketone organic matter, liquid nitrile organic matter, tetrahydrofuran or dimethyl sulfoxide.
4. The surface modification method of the silicon-carbon negative electrode material according to claim 1, characterized in that: In the modifier solution, the first sintering treatment time is 24 to 48 hours.
5. The surface modification method of the silicon-carbon negative electrode material according to claim 1, characterized in that: In the modifier solution, the mass ratio of the modifier solution to the sintered silicon-carbon negative electrode material is 1:(0.01-1.0), preferably 1: (0.2~0.5)。 6. The surface modification method of the silicon-carbon negative electrode material according to claim 1, characterized in that: In the modifier solution, the second sintering treatment time is 12 to 72 hours.
7. A modified silicon-carbon negative electrode material, characterized in that: Obtained by the surface modification method according to any one of claims 1 to 6.
8. A negative electrode sheet, comprising a current collector and an active layer attached to the surface of the current collector, characterized in that: The active material in the active layer is the modified silicon-carbon negative electrode material according to claim 7.
9. The negative electrode sheet according to claim 8, characterized in that: The modified silicon-carbon negative electrode material, the conductive agent, the binder, and the thickener are added to a solvent and mixed evenly to obtain a slurry, and the slurry is coated on the surface of the current collector and dried.
10. A lithium ion battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The negative electrode sheet is the negative electrode sheet according to claim 8 or 9.
Citation Information
Patent Citations
Lithium ion battery negative electrode material, preparation method thereof and lithium ion battery
CN119059514A